A long-term corrosion barrier with an insulating boron nitride monolayer. Issue 14 (22nd March 2016) - Shen, Liting; Zhao, Yuda; Wang, Yi; Song, Ruobing; Yao, Qian; Chen, Shanshan; Chai, Yang
Abstract : Insulating hexagonal boron nitride suppresses the electrochemical corrosion and provides a more effective long-term corrosion barrier than graphene. Abstract : Graphene has been demonstrated as an ultrathin and light-weight corrosion barrier because of its high impermeability. However, it fails to prevent the Cu corrosion over a long term because the high conductivity of graphene enables the formation of a galvanic cell and promotes the electrochemical reaction. Here we theoretically and experimentally study a boron nitride (BN) monolayer as a long-term corrosion barrier for Cu. Our density functional theory calculations show that the potential barrier for O2 to pass through BN is close to that of graphene. The long-term barrier characteristics of BN and graphene are comparably evaluated by aging in an ambient environment for 160 days. Morphological and spectroscopic characterization shows that a BN monolayer has much better long-term barrier performance than graphene. X-ray photoelectron spectroscopy analysis shows that the Cu 2+ percentage of the aging Cu sample with a BN barrier is reduced by around 15 times compared with that covered by graphene. The superior long-term barrier performance of a BN monolayer can be understood to be a result of its high impermeability and insulating characteristics, which suppress the galvanic corrosion under the ambient environment. These studies reveal that a BN monolayer is a more effective long-term corrosion barrier than graphene.